Distinctive Features and Design for Mathematics Learning Mobile Games in Elementary School Students - Gilly Marlya Tiwow; Djubir R E Kembuan; J R Batmetan (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This paper assesses the implementation of the framework for building new Distinctive Features and design mathematics games. We explain how to design a typical mathematics game according to the learning needs of elementary school students. Next, we explain how to build new Distinctive features that are unique to students’ needs and can be run in math games. We explain the importance of constructing mathematics game features and designs that suit the characteristics of primary school students. We conclude that the selection of distinctive features and game design according to students’ needs are the most important aspects in building an interesting mathematics learning experience. This conclusion was obtained from the results of usability tests on elementary school students. This paper has broad implications in the development of elementary school games.